Structural response of initially loaded RC beam to different retrofitting techniques - Thanoon, Waleed Abdulmalik; Jaafar, Mohd Saleh; Noorzaei, Jamaloddin; Abdul Kadir, Mohd Razali; Mohammed, Thamer Ahmed (Universiti Putra Malaysia Press, 2004)
The increase in the large number of distressed reinforced concrete structure underscores the importance of developing acceptable retrofitting techniques. This study investigates the structural behaviour of full scale reinforced concrete beams strengthened by two different techniques. The first technique used is the strengthening of the beam by CFRP, while the second technique used is the external pre-stressing. The specimens were initially loaded to two-thirds of their predicted ultimate flexural capacity. They were then unloaded and strengthened with either CFRP or external prestressing. The beams were subsequently subjected to incremental loads until failure. The structural response of the tested specimens had been found in terms of their cracking behaviour, load-deflection relationship, ductility, strain, distribution, ultimate load and failure mechanism. The results indicate similar structural response in both retrofitting techniques at the ultimate range. Hence the concept of elastic design used in prestressed concrete members may be used for reinforced concrete members strengthened with CFRP.